Beobachtungen über die Inselberge bei Hua-Hin am Golf von Siam - Louis, Herbert (ERDKUNDE, 1959)
Observations near Hua-Hin West of the Gulf of Siam show that the granitic inselbergs found there have been formed by gradual retrogressive enlargement of the origins of flat swale-shaped valleys. Weathering consists mainly in granular disintegration proceeding fastest in fissured rocks. Steep slopes drying more quickly are more resistant to it than smooth ones. Under these circumstances the efficacious rain-wash removing the granitic sand brings about steep slopes on the one side and gently rolling erosion surfaces on the other, which are sculptured by wide open valleys with sides flaring out separated by very smooth swells, and which owe their specific relief pattern to rill wash (in German the present author proposes the descriptive denomination “flache Fußfluren for them). They are clearly different from the conoplain-shaped pediments of arid climate formed by lateral corrasion of ephemeral overburdened braided rivers. The regressive enlargement of the valley heads due to granular disintegration following fissures thus forming wide flat-bottomed valleys favours the separation of singular inselbergs from a more extended rock massive. The valleys frequently coalescing in low valley watersheds, which form a characteristic relief feature of inselberg landscapes become comprehensible, since the same structurally conditioned zones of weakness can be attacked from different ramps.